Influence of teacher availability on student academic achievement in public secondary schools in Southwestern Nigeria - Hazzan , Moses Kayode (American Journal of Education and Learning, 2024)
This study investigated the influence of Teacher Availability -TAV (Number of Available Teachers, Teacher Punctuality -TP, Teacher Promptness to Class -TPC) on Student Academic Achievement (SAA) in Public Senior Secondary Schools (PSSS) in Southwestern Nigeria. The purpose of the study was to investigate the influence of teacher availability on the student’s academic achievement in public secondary schools in Southwestern Nigeria. The descriptive survey research design of correlational type was adopted while the multi-stage sampling procedure was used in the study. A simple random sampling technique was used to select three (Oyo, Ogun, and Ekiti) states out of the six in Southwestern Nigeria, as well as one Senatorial District (SD) from each state. The technique of proportionate-to-size sampling was employed to select 40% of the Local Government Areas (LGAs) in each SD and 50% (101) of the schools in the sampled LGAs. A class of 3,030 PSSS II was used; 202 Mathematics and English Language teachers and 202 Heads of Department were purposively sampled, while 101 school administrators were enumerated. The instruments were TP, TPC, English Language Achievement Test-ELAT, and Mathematics Achievement Test-MAT. The results revealed that SAA was low while TAV was high against the threshold of 2.5. The results equally showed that TAV significantly contributed to SAA. Based on the findings, it was recommended that the recruitment of teachers should be practically based on merit (in terms of educational qualifications). The school authorities should ensure that teacher availability (teacher punctuality and promptness to class) is sustained to improve the SAA.